Andy Russell, Not Wanted by the Police - Adler, David A. (San Diego Harcourt, Inc., 2001)
Andy and Tamika are watching their neighbor's house while they are away, but when strange and troubling things start happening inside the house, the police do not believe the children.
1 - 6
Keywords: Mystery and detective stories; Neighbors - Fiction; Schools - Fiction